Aktivitas Tabir Surya Ekstrak Biji Nyamplung (Chalophyllum inophyllum Linn) - Yusran Khery; Aliefman Hakim; Joni Rokhmat; AA Sukarso (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to evaluate the sunscreen activity of nyamplung seed extract resulting from cold press extraction, soxletation with n-hexane solvent, and maceration with alcohol solvent. Apart from that, determining the minimum concentration of using nyamplung seed extract as a sunscreen ingredient. This study was conducted in vitro using UV spectrophotometry with the method developed by Sayre et al., (1979). The results showed that the alcohol extract of nyamplung seeds had the best sunscreen activity with an SPF of 42,499 at a concentration of 1,000 ppm in chloroform:alcohol (1:1) in the ultra protection category. Followed by n-hexane extract and cold pressed extract with SPF 39,951 and 36,349 respectively with the same concentration, solvent, and category. The higher the sample concentration, the lower the percentage of erythema and pigmentation, while the higher the SPF. The lowest concentrations of cold pressed extract, n-hexane, and nyamplung seed alcohol that meet the category of sunscreen with ultra protection were 600, 600, and 400 ppm, respectively.